Implementasi API Payment Gateway Midtrans pada Sistem Reservasi Dokter Gigi Berbasis Mobile - Bilal Nurul Fauzi; Muhammad Fachrie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Common problems with dental clinics include large queues of patients, lack of optimization of patient administration, and manual payment systems that make it difficult for patients. A mobile-based dental clinic reservation application that is integrated with the Midtrans payment system is a solution to the difficulty of administering reservations at dental clinics, reducing patient queue problems, and optimizing payments. This research method consists of problem identification, system analysis, system design, implementation, and testing. System implementation uses Android Studio software with the Kotlin programming language and the Jetpack Compose framework. Payment implementation using midtrans API services. For data storage and management using Firebase Firestore. There are two users, namely patient and admin, each of whom has a different role. Patients can make new reservations and make payments, while admins can accept or reject reservations and payments. Application testing is carried out using the black box testing method. The test results show that the application successfully passed the test for each parameter tested.